Oxidation of Several p-Phenylenediamines in Room Temperature Ionic Liquids: Estimation of Transport and Electrode Kinetic Parameters - Long, J.; Silvester, Debbie; Barnes, A.; Rees, N.; Aldous, L.; Hardacre, C.; Compton, R. (American Chemical Society, 2008)
The electrochemical oxidation of N,N,N‘,N‘-tetramethyl-p-phenylenediamine (TMPD) has been studied by cyclic voltammetry and potential step chronoamperometry at 303 K in five ionic liquids, namely [C2mim][NTf2], [C4mim][NTf2], [C4mpyrr][NTf2], [C4mim][BF4], and [C4mim][PF6] (where [Cnmim]+ = 1-alkyl-3-methylimidazolium, [C4mpyrr]+ = N-butyl-N-methylpyrrolidinium, [NTf2]- = bis(trifluoromethylsulfonyl)imide, [BF4]- = tetrafluoroborate, and [PF6]- = hexafluorophosphate). Diffusion coefficients, D, of 4.87, 3.32, 2.05, 1.74, and 1.34 × 10-11 m2 s-1 and heterogeneous electron-transfer rate constants, k0, of 0.0109, 0.0103, 0.0079, 0.0066, and 0.0059 cm s-1 were calculated for TMPD in [C2mim][NTf2], [C4mim][NTf2], [C4mpyrr][NTf2], [C4mim][BF4], and [C4mim][PF6], respectively, at 303 K. The oxidation of TMPD in [C4mim][PF6] was also carried out at increasing temperatures from 303 to 343 K, with an activation energy for diffusion of 32.3 kJ mol-1. k0 was found to increase systematically with increasing temperature, and an activation energy of 31.4 kJ mol-1 was calculated. The study was extended to six other p-phenylene-diamines with alkyl/phenyl group substitutions. D and k0 values were calculated for these compounds in [C2mim][NTf2], and it was found that k0 showed no obvious relationship with the hydrodynamic radius, r.